Examining user fee reductions in public primary healthcare facilities in Kenya, 1997–2012: effects on the use and content of antenatal care - Mardieh L. Dennis; Lenka Benova; Catherine Goodman; Edwine Barasa; Timothy Abuya; Oona M. R. Campbell (International Journal for Equity in Health, 2020)
Abstract Background In 2004, The Kenyan government removed user fees in public dispensaries and health centers and replaced them with registration charges of 10 and 20 Kenyan shillings (2004 $US 0.13 and $0.25), respectively. This was termed the 10/20 policy. We examined the effect of this policy on the coverage, timing, source, and content of antenatal care (ANC), and the equity in these outcomes. Methods Data from the 2003, 2008/9 and 2014 Kenya Demographic and Health Surveys were pooled to investigate women’s ANC care-seeking. We conducted an interrupted time series analysis to assess the impact of the 10/20 policy on the levels of and trends in coverage for 4+ ANC contacts among all women; early ANC initiation and use of public facility-based care among 1+ ANC users; and use of public primary care facilities and receipt of good content, or quality, of ANC among users of public facilities. All analyses were conducted at the population level and separately for women with higher and lower household wealth. Results The policy had positive effects on use of 4+ ANC among both better-off and worse-off women. Among users of 1+ ANC, the 10/20 policy had positive effects on early ANC initiation at the population-level and among better-off women, but not among the worse-off. The policy was associated with reduced use of public facility-based ANC among better-off women. Among worse-off users of public facility-based ANC, the 10/20 policy was associated with reduced use of primary care facilities and increased content of ANC. Conclusions This study highlights mixed findings on the impact of the 10/20 policy on ANC service-seeking and content of care. Given the reduced use of public facilities among the better-off and of primary care facilities among the worse-off, this research also brings into question the mechanisms through which the policy achieved any benefits and whether reducing user fees is sufficient for equitably increasing healthcare access.